The Prone position in cardiophatic patients: a literature survey - Ferreira Taino, Bruno; Bezerra Nogueira, Ivan Daniel; de Oliveira, Márcio Aparecido; de Miranda Silva Nogueira, Patrícia Angélica (O Mundo da Saúde, 2008)
The prone position seems to be a promising strategy to improve hypoxemia in patients with acute pulmonary injuries and acute respiratory discomfort syndrome. Studies have shown that, during its application, the ventilation of areas previously atelectasied occurs and is followed by blood flow redistribution with a reduction of intrapulmonary shunt, causing an improvement in the ventilation/ perfusion relationship. The authors made a survey on the use of the prone position, its indications and contraindications, as well as the mechanisms involved in the improvement of the oxygenation of cardiopathic patients.